(untitled) (Swiss Medical Weekly, 2019)
The objectives were to determine urinary iodine concentration (UIC) in day and night samples collected over a 24-hour period and evaluate the usual dietary iodine intake distribution from this collection. We propose a method by which the prevalence of inadequacy can be calculated from a single 24-hour collection, reducing the burden on participants and the study costs. The samples from 1128 participants were collected between 2009 and 2013 within the framework of the Swiss Kidney Project on Genes observational cohort study; 1024 samples were suitable for statistical evaluation of iodine analysis. Participants were over 18, resident in Switzerland and of European ancestry. Over 24 hours, urine was collected as night-time (bedtime until and including first morning urine) and day-time (the remainder) samples. Associations with variables, in particular to estimated glomerular filtration rate (eGFR), were investigated using mixed models. The 24-hour median UICs were 73 and 96 µg/l for women (n = 542) and men (n = 482), respectively; 24-hour median intakes (derived from the corresponding excretion) were 127 and 156 µg/d, respectively. Day and night excretions were normalised to 24-hour excretion values and the usual intake distribution calculated by the US National Cancer Institute method. The Estimated Average Requirement cut-point method was used to calculate the prevalence of inadequacy, estimated at 14% for women and 4% for men; above the target of 2-3%. We conclude that segregating 24-hour urine into day and night collections is sufficient to determine the prevalence of iodine inadequacy in the population and reduces the burden on participants by sparing a second 24-hour collection. No association between iodine intake and eGFR was found.